2022
DOI: 10.11609/jott.5490.14.5.21043-21054
|View full text |Cite
|
Sign up to set email alerts
|

Bionomics study of Mansonia (Diptera: Culicidae) in a filariasis-endemic area of Sedang Village, Banyuasin Regency, South Sumatra, Indonesia

Abstract: An investigation of bionomic study of Mansonia species was successfully conducted in Sedang village which is one of the filariasis-endemic areas in Indonesia. The study was carried out for 14 months from April 2017 to May 2018. In order to trap the local mosquitoes in the study area, indoor and outdoor human landing collection method was adopted.  During the study, 7,908 mosquitoes were collected which consisted of 13 genera and 40 species of mosquitoes. Moreover, Mansonia uniformis, M. annulifera, and M. indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Research conducted in Banyuasin, South Sumatra, Indonesia, by analyzing lymphatic filariasis vectors through PCR tests confirmed that only Mansonia annulifera was detected as positive as a lymphatic filariasis vector. In that study, Brugia malayi was detected as captured Mansonia annulifera (39). This corresponds to the data provided by the Indonesian Ministry of Health, indicating that Brugia malayi is responsible for 70% of lymphatic filariasis cases in Indonesia (40).…”
Section: Vector Of Lymphatic Filariasissupporting
confidence: 87%
“…Research conducted in Banyuasin, South Sumatra, Indonesia, by analyzing lymphatic filariasis vectors through PCR tests confirmed that only Mansonia annulifera was detected as positive as a lymphatic filariasis vector. In that study, Brugia malayi was detected as captured Mansonia annulifera (39). This corresponds to the data provided by the Indonesian Ministry of Health, indicating that Brugia malayi is responsible for 70% of lymphatic filariasis cases in Indonesia (40).…”
Section: Vector Of Lymphatic Filariasissupporting
confidence: 87%